Abuse of Official Position - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
Lawful, effective, efficient, prompt and adequate acting of officials and responsible persons when performing public authorisations and official duties they are entrusted represents a ground and a guarantee for the functioning of public services and state bodies in general. That is the reason why it is necessary that officials (both national and foreign) and responsible persons in state bodies, organisations, and communities act within their official authorisations in a lawful and efficient manner. Not only do the infringement and abuse of these authorisations represent the violation of other natural and legal persons’ rights and interests protected by the law, but they also represent a way of harming or threatening perpetrators’ official duty. In that way, the criminal offence named Abuse of Office is committed. Starting from the ancient written legal sources, numerous contemporary legislations, including the legislation of the Republic of Serbia, have been familiar with this criminal offence. This paper discusses the definition, characteristics, and contents of the fundamental criminal offence against official duty known as Abuse of Office from both theoretical and practical points of view.